P2-type medium-entropy layered oxide positive electrode material and preparation method and application thereof
Through entropy regulation and artificial CEI strategy, multivalent ions were introduced and NaTaO3 protective layer was constructed, which solved the capacity attenuation and electrochemical performance deterioration of P2-type layered oxide positive electrode materials under high pressure conditions, and achieved the high aerial stability and all-climate adaptability of the material.
Patent Information
- Application Number
- CN202510121180.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-26
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-26
AI Technical Summary
The P2 layered oxide cathode material has problems of capacity attenuation and deterioration of electrochemical properties under high pressure conditions, and the material's air sensitivity and all-climate adaptability are insufficient, which limits its commercialization process.
Through the dual-function strategy of entropy regulation and artificial CEI (positive electrolyte interface), multivalent ions (Li/Mg/Ta) are introduced and NaTaO3 protective layer is constructed on the surface to jointly improve the structural stability and all-climate performance of the material.
The high aerial stability and all-climate adaptability of the P2 medium-entropy layered oxide cathode material under high pressure conditions is achieved, extending its cycle life and improving electrochemical performance.
Smart Images

Figure CN119890294A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of positive electrode materials, and specifically discloses a P2 type medium entropy layered oxide positive electrode material and a preparation method and application thereof. Background Art
[0002] Sodium-ion batteries have become one of the most promising candidates for next-generation large-scale energy storage applications, in which cathode materials play a crucial role in determining specific capacity and operating voltage. x TMO2 has attracted wide attention due to its simple synthesis process and excellent electrochemical performance. + The coordination environment can x TMO2 is divided into P2 type and O3 type materials. 2 / 3 Ni 1 / 3 Mn 2 / 3 O2 (NM) cathode materials have high theoretical specific capacity and excellent Na + Diffusion dynamics stands out as a typical representative material of P2 type.
[0003] However, in the pursuit of higher energy density, expanding the voltage operating range will lead to serious capacity attenuation and deterioration of electrochemical performance, which restricts the application of NM. At the same time, the air sensitivity and all-weather adaptability of layered oxide materials are also major bottlenecks in their practical application. On the one hand, long-term exposure to humid air will lead to performance degradation, shortened life and increased storage and maintenance costs. On the other hand, poor temperature adaptability also limits its practical application in extreme environments. These problems seriously restrict the commercialization process of layered oxide materials.
[0004] At present, atomic doping (Li, Mg, Ti, Cu, etc.) and surface coating (oxide, phosphate, fluoride, etc.) strategies have been proven to effectively alleviate the instability of NM under high pressure and extend its cycle life. However, these single modification strategies have their own limitations. Although the surface coating can build a protective layer at the interface of the positive electrode material to reduce side reactions, it cannot effectively inhibit the structural degradation caused by the irreversible phase transition of P2-O2 under high voltage. The doping strategy is also difficult to effectively prevent the occurrence of interface side reactions.
[0005] A Chinese patent (CN202211068356.X) reports a core-shell structure in which a P2-type oxide layer is in situ grown on the surface of an O3-type oxide layer. The material in this patent is a composite phase structure of P2-O3, and the preparation method is complex and the conditions are harsh. In addition, existing studies pay little attention to the air sensitivity and all-weather performance of materials under high voltage. Therefore, in response to the above problems, it is urgent to develop an effective comprehensive modification strategy to improve the air sensitivity and all-weather adaptability of P2-type layered oxide positive electrode materials under high-pressure conditions. Summary of the invention
[0006] In order to solve the above problems, the present invention discloses a P2-type medium entropy layered oxide cathode material and its preparation method and application. The dual-functional strategy of entropy regulation and artificial CEI is adopted to synergistically improve the air stability and all-weather performance of the material to adapt to extreme environments.
[0007] The technical solution of the present invention is as follows: A P2 type medium entropy layered oxide positive electrode material, the structural formula of the positive electrode material is Na f Li a Mg b Ni c Mn d Ta e O2, where 0.05≤a≤0.1, 0.05≤b≤0.1, 0.13≤c≤0.23, 0.63≤d≤0.66, 0.01≤e≤0.04, 0.67≤f≤0.75, and a+b+c+d+e=1, a+b+c=0.33.
[0008] The configuration entropy of the cathode material depends on the number and molar fraction of the elements. According to the configuration entropy calculation, the entropy value of the cathode material in the present invention is 1.22 R, which is higher than 0.9 R of NM, and belongs to medium entropy material. Higher configuration entropy means lower Gibbs free energy, which is conducive to improving the structural stability of the material.
[0009] Preferably, the surface of the positive electrode material has a NaTaO3 phase as an artificial CEI protective layer.
[0010] Preferably, the structural formula of the positive electrode material is Na 0.72-0.75 Li 0.1 Mg 0.05 Ni 0.18 Mn 0.66-0.63 Ta 0.01-0.04 O2.
[0011] The preparation method of the above-mentioned P2 type medium entropy layered oxide positive electrode material comprises the following steps: S1. Ball milling the sodium source, lithium source, magnesium oxide, nickel oxide, manganese oxide and tantalum source in a measured ratio with ethanol as a dispersion medium to obtain a uniformly mixed precursor; S2, after the precursor is dried, press it into a sheet; S3, calcining the flake precursor at 900-1000°C and cooling it to obtain the product.
[0012] Preferably, the calcination time is 12-20 h.
[0013] Preferably, the calcination temperature is 950°C.
[0014] Preferably, the sodium source includes any one of sodium carbonate and sodium acetate.
[0015] Preferably, the lithium source includes any one of lithium carbonate and lithium hydroxide.
[0016] Preferably, the tantalum source includes any one of tantalum pentoxide and tantalum ethoxide.
[0017] Preferably, the cooling is specifically: lowering the temperature to below 100° C., taking out, transferring to a protective atmosphere and cooling to room temperature.
[0018] A sodium ion battery comprises the above-mentioned P2 type intermediate entropy layered oxide positive electrode material.
[0019] The advantages of the present invention are as follows: The present invention uses a dual-functional strategy based on entropy regulation and artificial cathode electrolyte interface (CEI) construction to achieve precise regulation of the structure of P2-type medium-entropy layered oxide cathode materials. The introduction of multivalent ions (Li / Mg / Ta) increases the configurational entropy of the material, effectively enhancing the structural stability and Na + The doping of Ta element not only increases the configuration entropy, but also forms an atomic-scale artificial NaTaO3CEI layer as a protective layer at the interface. The artificial CEI layer enhances the structural stability of the surface and interface and effectively inhibits the interface side reactions. Therefore, through the synergistic effect of entropy regulation and artificial CEI layer, Na f Li a Mg b Ni c Mn d Ta e O2 exhibits excellent air stability and all-weather performance, providing new ideas for the development of sodium-ion batteries for use in extreme environments.
[0020] The electrochemical performance test of the present invention was carried out in the voltage range of 2-4.35V, and the results showed that the positive electrode material has excellent high-voltage stability. The working characteristics of the wide voltage window are helpful to improve the energy density of the battery and have good industrial application prospects.
[0021] The present invention also provides a one-pot method for preparing a P2 type medium entropy layered oxide positive electrode material. The preparation method is simple, the raw materials are simple and easy to obtain, the preparation process has low requirements on equipment, the production cost is low, and it is easy to apply industrially. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 XRD spectra of LMNMT, 2% T-LMNMT, 4% T-LMNMT and NM in the present invention; Figure 2 HRTEM image of LMNMT in the present invention; Figure 3 is a graph showing the variation of the Ta / Mn and Ta / Ni ratios of LMNMT in the present invention with etching time; Figure 4 Comparison of the cycle performance (0.5 C) of LMNMT with different Ta contents in the present invention; Figure 5 The cycling performance of LMNMT and NM at 40°C (a) and -20°C (b) and wide temperature range performance (c) at 1 C current density in the present invention; Figure 6 Comparison of the cycle performance (2 C) of LMNMT with different Li / Mg contents in the present invention; Figure 7 The cycle performance of the samples of LMNMT and NM treated in water and air at 2°C in the present invention; Figure 8 This is the wide temperature range performance of LMNMT and LM21NM in the present invention after 7 hours of water treatment. DETAILED DESCRIPTION
[0023] The technical solutions in the implementation cases of the present invention are described clearly and completely below. The described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] In the present invention, "all-weather performance" refers to the electrochemical performance of a battery at different temperatures.
[0025] The reagents or instruments used in the examples of the present invention without indicating the manufacturer are all conventional reagent products that can be obtained through commercial purchase.
[0026] Example 1: A P2-type medium entropy layered oxide positive electrode material having a structural formula of Na 0.75 Li 0.1 Mg 0.05 Ni 0.18Mn 0.66 Ta 0.01 O2, the preparation method thereof is: Na2CO3, Li2CO3, MgO, NiO, MnO2, and Ta2O5 were wet-milled at 350 rpm for 1 h according to the designed stoichiometric ratio, and 2 ml of ethanol was used as the dispersion medium to obtain a uniformly mixed precursor. The obtained precursor was dried in a vacuum oven at 60 ° C for 12 h. Subsequently, 0.3 g of the precursor was weighed and placed in a round mold, pressed into a sheet under a pressure of 16 MPa, and transferred to a muffle furnace for calcination at 950 ° C for 15 h. When the temperature dropped to 100 ° C, it was quickly transferred to a glove box filled with argon for storage, and finally the target product, a P2-type medium-entropy layered oxide (named LMNMT) coated with NaTaO3, was obtained.
[0027] Example 2: A P2-type medium entropy layered oxide positive electrode material having a structural formula of Na 0.74 Li 0.1 Mg 0.05 Ni 0.18 Mn 0.65 Ta 0.02 O2, the preparation method thereof is: Na2CO3, Li2CO3, MgO, NiO, MnO2, and Ta2O5 were wet-milled at 350 rpm for 1 h according to the designed stoichiometric ratio, and 2 ml of ethanol was used as the dispersion medium to obtain a uniformly mixed precursor. The obtained precursor was dried in a vacuum oven at 60 ° C for 12 h. Subsequently, 0.3 g of the precursor was weighed and placed in a round mold, pressed into a sheet under a pressure of 16 MPa, and transferred to a muffle furnace for calcination at 900 ° C for 20 h. When the temperature dropped to 100 ° C, it was quickly transferred to a glove box filled with argon for storage, and finally the target product, a P2-type medium-entropy layered oxide coated with NaTaO3 (named 2% T-LMNMT), was obtained.
[0028] Example 3: A P2-type medium entropy layered oxide positive electrode material having a structural formula of Na 0.72 Li 0.1 Mg 0.05 Ni 0.18 Mn 0.63 Ta 0.04 O2, the preparation method thereof is: Na2CO3, Li2CO3, MgO, NiO, MnO2, and Ta2O5 were wet-milled at 350 rpm for 1 h according to the designed stoichiometric ratio, and 2 ml of ethanol was used as the dispersion medium to obtain a uniformly mixed precursor. The obtained precursor was dried in a vacuum oven at 60 ° C for 12 h. Subsequently, 0.3 g of the precursor was weighed and placed in a round mold, pressed into a sheet under a pressure of 16 MPa, and transferred to a muffle furnace for calcination at 1000 ° C for 12 h. When the temperature dropped to 100 ° C, it was quickly transferred to a glove box filled with argon for storage, and finally the target product, a P2-type medium-entropy layered oxide coated with NaTaO3 (named 4% T-LMNMT), was obtained.
[0029] Example 4: A P2-type medium entropy layered oxide positive electrode material having a structural formula of Na 0.72 Li 0.07 Mg 0.05 Ni 0.21 Mn 0.66 Ta 0.01 O2, prepared in the same manner as in Example 1 (named LM75NMT).
[0030] Example 5: A P2-type medium entropy layered oxide positive electrode material having a structural formula of Na 0.7 Li 0.05 Mg 0.05 Ni 0.23 Mn 0.66 Ta 0.01 O2, prepared as in Example 1 (named LM55NMT).
[0031] Example 6: A P2-type medium entropy layered oxide positive electrode material having a structural formula of Na 0.7 Li 0.05 Mg 0.07 Ni 0.21 Mn 0.66 Ta 0.01 O2, prepared in the same manner as in Example 1 (named LM57NMT).
[0032] Comparative Example 1: A P2-type layered oxide positive electrode material having a structural formula of Na 0.67 Ni 0.33 Mn 0.67 O2, prepared as in Example 1 (named NM).
[0033] Comparative Example 2: A P2-type medium-entropy layered oxide positive electrode material having a structural formula of Na 0.76 Li 0.1 Mg 0.05 Ni 0.18 Mn 0.67 O2, prepared as in Example 1 (named LM21NM).
[0034] Performance Testing The P2 type medium entropy layered oxide positive electrode material prepared in Example 1-3 was subjected to XRD analysis, and the results were as follows: Figure 1 As shown. With the increase of Ta content, the 4%T-LMNMT sample showed additional weak diffraction peaks near 23°, 53° and 58°. These diffraction peaks can be attributed to the diffraction peaks of NaTaO3 (PDF# 01- 0774 -2479), indicating that an artificial NaTaO3CEI layer is formed on the surface of the positive electrode material due to the introduction of Ta. At the same time, the other peaks all match the P2 phase well. The results show that the layered oxide positive electrode material LMNMT provided by the present invention is a P2 phase and has an artificial CEI NaTaO3 modification on the surface.
[0035] The LMNMT prepared in Example 1 was characterized as follows: Figure 2 As shown in Figure 1, the HRTEM image of LMNMT shows that region I exhibits clear lattice fringes with a plane spacing of 0.26 nm, corresponding to the (100) crystal plane of the P2-type structure. A uniform coating with a thickness of about 4 nm was observed on the surface of the material, in which the lattice fringes in region II had a plane spacing of 0.19 nm, matching the (100) crystal plane of NaTaO3. This result confirms the successful construction of a P2-type intermediate entropy layered oxide cathode material with an artificial NaTaO3CEI layer.
[0036] By Ar + Etching X-ray photoelectron spectroscopy (XPS) further investigated the interface composition of LMNMT. Figure 3 As shown, with the increase of etching time, the ratios of Ta / Ni and Ta / Mn decreased, confirming the existence of NaTaO3 protective layer on the surface of LMNMT.
[0037] Experimental Example 1 Effect of different Ta contents on the performance of positive electrode materials The positive electrode material (LMNMT, 2% T-LMNMT, 4% T-LMNMT and NM): conductive carbon black: PVDF = 75:15:10 was made into a slurry and coated on aluminum foil. After vacuum drying for 12 hours, a 2032-type battery was assembled in a glove box. The electrolyte was 1M NaClO4+EC / PC (1:1) v / v+5% FEC. The electrochemical performance test was carried out in the temperature range of -20℃ to 40℃. The voltage working range is 2-4.35V.
[0038] Figure 4 The cycling performance of LMNMT with different Ta contents at 0.5 C current density is shown. It can be seen that LMNMT has the best cycling stability and is significantly better than NM, indicating that the dual strategy can significantly improve the high-voltage cycling stability of the positive electrode material.
[0039] Wide temperature range testing is done in a high and low temperature chamber with variable temperature control. Figure 5 The high and low temperature cycling performance and wide temperature range performance of LMNMT and NM at 1C current density are shown. Figure 5 As shown in Figures 5a and 5b, after 100 cycles at 40 °C, the capacity of LMNMT is almost twice that of NM. In addition, after 100 cycles at -20 °C, the discharge capacity of LNMNT is still 57 mAhg -1 , while the discharge capacity of NM is close to 0. Figure 5 As shown in Figure 3, LMNMT exhibits better adaptability to temperature. Based on the above results, LMNMT exhibits excellent all-weather performance (-20℃-40℃) compared with NM.
[0040] Experimental Example 2 Effect of different Li / Mg contents on the performance of positive electrode materials The positive electrode material (LMNMT, LM75NMT, LM55NMT and LM57NMT): conductive carbon black: PVDF = 75:15:10 was made into a slurry and coated on aluminum foil. After vacuum drying for 12 hours, 2032 type batteries were assembled in a glove box. The electrolyte was 1M NaClO4+EC / PC (1:1) v / v+5% FEC; the test conditions were: voltage operating range of 2-4.35V, current density of 2C.
[0041] like Figure 6 As shown in Figure 2, different Li / Mg contents have little effect on the performance of the positive electrode material. When the Li / Mg ratio is 2:1, the performance is optimal.
[0042] Experimental Example 3 Air Stability LMNMT, LM21NM, and NM were immersed in water for 1h and 7h, and exposed to air for 7 days to obtain the corresponding samples LMNMT-Water-1h, LMNMT-Water-7h, LMNMT-Air-7d, LM21NM-Water-7h, NM-Water-1h, NM-Water-7h, and NM-Air-7d; Referring to Experimental Example 1, 2032 type batteries were assembled, and the electrolyte was 1M NaClO4+EC / PC (1:1) v / v+5% FEC. The electrochemical performance test was carried out in the temperature range of -20℃ to 40℃. The wide temperature range test was completed based on a high and low temperature box with variable temperature control, and the voltage working range was 2-4.35V.
[0043] like Figure 7As shown in the figure, at 2 C, the cycling performance of NM is significantly attenuated after water treatment and air exposure. The capacity retention rates of 200 cycles after 1h and 7h water treatment are 74.6% and 72.9%, respectively; the capacity retention rate after 7d air exposure is 64.8%, showing poor tolerance. In contrast, the capacity retention rate of LMNMT after water / air exposure treatment can still be maintained at a high level (water-1h: 91.3%; water-7h: 95.9%; Air-7d: 84.8%), confirming that the material has excellent water / air stability. This is mainly because the construction of the artificial CEI layer as a protective layer can effectively prevent LMNMT from being directly exposed to air / water, further improving the surface / interface stability of the material.
[0044] like Figure 8 As shown in the figure, after water treatment, the high and low temperature resistance of LM21NM is poor. Compared with LM21NM, LMNMT has the introduction of Ta, and the construction of an artificial NaTaO3CEI protective layer on the surface is beneficial to improve the surface / interface stability, thereby improving the all-weather performance of the positive electrode material.
[0045] The above-mentioned embodiments only express a limited number of preferred implementations of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A P2 type medium entropy layered oxide positive electrode material, characterized in that: The structural formula of the positive electrode material is Na f Li a Mg b Ni c Mn d Ta e O2, where 0.05≤a≤0.1, 0.05≤b≤0.1, 0.13≤c≤0.23, 0.63≤d≤0.66, 0.01≤e≤0.04, 0.67≤f≤0.75, and a+b+c+d+e=1, a+b+c=0.
33.
2. The P2 type medium entropy layered oxide positive electrode material according to claim 1, characterized in that: The surface of the positive electrode material has a NaTaO3 phase.
3. The P2 type medium entropy layered oxide positive electrode material according to claim 1, characterized in that: The structural formula of the positive electrode material is Na 0.72-0.75 Li 0.1 Mg 0.05 Ni 0.18 Mn 0.66-0.63 Ta 0.01-0.04 O2.
4. The method for preparing the P2 type medium entropy layered oxide positive electrode material according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1. Ball milling the sodium source, lithium source, magnesium oxide, nickel oxide, manganese oxide and tantalum source in a measured ratio with ethanol as a dispersion medium to obtain a uniformly mixed precursor; S2, after the precursor is dried, press it into a sheet; S3, calcining the flake precursor at 900-1000°C and cooling to obtain.
5. The preparation method according to claim 4, characterized in that: The calcination time is 12-20h.
6. The preparation method according to claim 4, characterized in that: The calcination temperature is 950°C.
7. The preparation method according to claim 4, characterized in that: The sodium source includes any one of sodium carbonate and sodium acetate.
8. The preparation method according to claim 4, characterized in that: The lithium source includes any one of lithium carbonate and lithium hydroxide.
9. The preparation method according to claim 4, characterized in that: The tantalum source includes any one of tantalum pentoxide and tantalum ethoxide.
10. A sodium ion battery comprising the P2-type intermediate entropy layered oxide positive electrode material according to any one of claims 1 to 3.
Citation Information
Patent Citations
P2 type sodium-ion battery positive electrode material modified by high-valence metal element, and preparation method and application of P2 type sodium-ion battery positive electrode material modified by high-valence metal element
CN115863559A
Sodium-ion battery positive electrode material and preparation method thereof
CN115986110A
Doping modified sodium-rich positive electrode material, preparation thereof, positive electrode plate and sodium ion battery
CN118352516A
High-entropy layered oxide material with anion-cation co-variable valence and preparation method and application of high-entropy layered oxide material
CN118825259A
Layered high-entropy oxide positive electrode material of sodium ion battery, preparation method of layered high-entropy oxide positive electrode material, positive electrode plate and sodium ion battery
CN119170795A